2007
DOI: 10.1094/phyto-97-0087
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Fusarium oxysporum f. sp. lactucae Inferred from Mitochondrial Small Subunit, Elongation Factor 1-α, and Nuclear Ribosomal Intergenic Spacer Sequence Data

Abstract: Fusarium oxysporum f. sp. lactucae, causal agent of Fusarium wilt of lettuce, is a serious pathogen recently reported in Arizona. Sequence analysis of the mitochondrial small subunit (mtSSU), translation elongation factor 1-alpha (EF-1alpha) gene, and the nuclear ribosomal DNA intergenic spacer (IGS) region was conducted to resolve relationships among f. sp. lactucae isolates, F. oxysporum isolates from other hosts, and local non-pathogenic isolates. Analysis of mtSSU sequences provided limited phylogenetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 29 publications
2
72
0
Order By: Relevance
“…IGS sequence polymorphisms contained much useful data for phylogenetic reconstruction and for inferring species limits with high discriminatory power within Fusarium as also previously noted by O'Donnell et al (22). The IGS has become one of the more popular loci for investigating genetic diversity or haplotypes nested within the FOSC (5,11,14) and, more recently, within the GFSC and other Fusaria spp. (16, 32).…”
Section: Vol 49 2011 Seven-locus Sequence Analysis Of Fusarium 1895mentioning
confidence: 73%
“…IGS sequence polymorphisms contained much useful data for phylogenetic reconstruction and for inferring species limits with high discriminatory power within Fusarium as also previously noted by O'Donnell et al (22). The IGS has become one of the more popular loci for investigating genetic diversity or haplotypes nested within the FOSC (5,11,14) and, more recently, within the GFSC and other Fusaria spp. (16, 32).…”
Section: Vol 49 2011 Seven-locus Sequence Analysis Of Fusarium 1895mentioning
confidence: 73%
“…This suggests that each VCG represents a clonal population (28,31,32). To determine further phylogenetic relationships within and among formae speciales of F. oxysporum DNA sequences of the mitochondrial small-subunit (mtSSU) rRNA gene, the ribosomal DNA (rDNA) intergenic spacer (IGS) region and the translation elongation factor (EF1-␣) gene have been used (33)(34)(35). Such studies confirmed multiple evolutionary origins for many formae speciales of F. oxysporum.…”
mentioning
confidence: 94%
“…The tests are, however, time consuming, labor intensive and subject to varying environmental or culture growth conditions during the experiments (Mbofung et al 2007;Woo et al 1996). Molecular techniques, such as restriction fragment analysis of PCR-amplified ribosomal intergenic spacers (IGS), can help to rapidly characterize large F. oxysporum populations (Edel et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Of the relatively small number of genes that have been used for phylogenetic studies within the Fusarium genus (e.g. IGS rDNA, elongation factor-1α, polygalacturonases, mitochondrial small subunit ribosomal RNA, phosphate permease, β-tubulin, nitrate reductase, MAT 1 and MAT2), the EF-1α (Amatulli et al 2010) and IGS rDNA genes (Mbofung et al 2007) seem adept for such application (O'Donnell et al 2009). The IGS region, which separates rDNA repeat units, is particularly suitable for studying intraspecific relationships (Appel and Gordon 1996;Mbofung et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation